STRUCTURAL TYPOLOGY IN MAKASSARESE FOLKTALES (Tipologi Struktural dalam Dongeng Makassar) - Hasina Fajrin R (Balai Bahasa Sulawesi Selatan, 2017)
Makassar folktales, one of local indigenous in South Sulawesi need to preserve and to study in order to maintain its existence. One way to analyze the folktales is using Alan Dundes theory. Dundes proposes motifeme sequences like lack, lack liquidated, deceit, deception, task, task accomplished, interdiction, violation, consequences, and attempted escape to describe the structural typology of the folktales. The writing is library research and applies descriptive qualitative method that relies on linguistic and employing meaning based of data analysis, whilst, the object is Rupama, a book written by Zainuddin Hakim. After analyzing it, the writer finds that the shortest structure of motifeme consists of lack (L) and lack liquidated (LL). Furthermore, folktales also represent that Makassar people believe that evil deed is always punished directly or indirectly. One interesting thing after analyzing the sequences, the attempted escape motifeme is only found once in the folktale. It shows that Makassar people prefer to face the problem frontally.